2008
DOI: 10.5032/jae.2008.01085
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Literacy: Clarifying a Vision for Practical Application

Abstract: "Agricultural literacy" is a working concept with considerable range in meaning and impact. An overview of agricultural literacy curricula shows complementary deductive and inductive approaches to the systematic incorporation of agricultural education in K-12 classrooms. Based on positions discussed at the 2005 Agricultural Literacy Special Interest Group meeting of the American Association for Agricultural Education, the authors identified three curricular approaches to promote agricultural literacy: (1) a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 4 publications
0
26
0
2
Order By: Relevance
“…These concept areas were societal and global significance of agriculture, public policy in agriculture, agriculture's relationship with the environment and natural resources, plant science, animal science, processing of agricultural products and marketing and distribution of agricultural products. Powell et al (2008) emphasized the reason of having no consensus on the definition of agricultural literacy as philosophical, political and epistemological differences among specialists. Based on the philosophical and epistemological differences, Powell et al (2008) reported three approaches to agricultural literacy from Agricultural Literacy Special Interest group meetings in 2005 and 2006.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…These concept areas were societal and global significance of agriculture, public policy in agriculture, agriculture's relationship with the environment and natural resources, plant science, animal science, processing of agricultural products and marketing and distribution of agricultural products. Powell et al (2008) emphasized the reason of having no consensus on the definition of agricultural literacy as philosophical, political and epistemological differences among specialists. Based on the philosophical and epistemological differences, Powell et al (2008) reported three approaches to agricultural literacy from Agricultural Literacy Special Interest group meetings in 2005 and 2006.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
“…Powell et al (2008) emphasized the reason of having no consensus on the definition of agricultural literacy as philosophical, political and epistemological differences among specialists. Based on the philosophical and epistemological differences, Powell et al (2008) reported three approaches to agricultural literacy from Agricultural Literacy Special Interest group meetings in 2005 and 2006. These approaches were programmed agricultural literacy (deductive model), emergent agricultural literacy (inductive model) and agriculturally literate value judgment (evaluative model).…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
“…The 1988 release of a National Research Council (NRC) report further crystalized agricultural literacy as a principal priority of the agricultural education field. Subsequently, a rich body of agricultural literacy research has been developed (e.g., Cannon, Broyles, Seibel, & Anderson, 2009;Colbath & Morish, 2010;Frick, Kahler, & Miller, 1991;Kovar & Ball, 2013;Meischen & Trexler, 2003;Powell, Agnew, & Trexler, 2008). To date, however, both research and practice have focused almost entirely on the infusion of agricultural concepts and principles into formal and non-formal k-12 curricula.…”
Section: Introductionmentioning
confidence: 99%
“…An individual possessing such knowledge would be able to synthesize, analyze, and communicate basic information about agriculture" (Frick, et al, 1991, p. 52). A subsequent report issued by the National Council on Agricultural Education (NCAE) in 2000 expanded the scope of the agricultural literacy agenda to include direct emphasis on the development of conversational competencies and age appropriate curricula (Meischen & Trexler, 2003;Powell, Agnew, & Trexler, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Agricultural Literacy Special Interest group of the American Association for Agricultural Education (AAAE) identified qualities of an agricultural literate person. This includes demonstration of fundamental agricultural knowledge that promote engagement in intellectual discussions on agriculture, thus making relevant decisions that are of great benefit to the society at large (Powell, Agnew & Trexler, 2008). The report of Frick (1990) identified an agricultural literate person as "an individual who would be able to synthesize, analyze, and communicate basic information about agriculture" (p. 52).…”
Section: Background Informationmentioning
confidence: 99%